Adipose-derived stem cells promote lymphangiogenesis in response to VEGF-C stimulation or TGF-ββ1 inhibition. (December 2011) - Yan, Alan; Avraham, Tomer; Zampell, Jamie C; Haviv, Yosef S; Weitman, Evan; Mehrara, Babak J
Aims: Recent studies have demonstrated that augmentation of lymphangiogenesis and tissue engineering hold promise as a treatment for lymphedema. The purpose of this study was to determine whether adipose-derived stem cells (ASCs) can be used in lymphatic tissue-engineering by altering the balance between pro- and anti-lymphangiogenic cytokines.Materials & methods: ASCs were harvested and cultured in media with or without recombinant VEGF-C for 48 h. ASCs were then implanted in mice using Matrigel plugs. Additional groups of animals were implanted with ASCs transfected with a dominant-negative TGF-ββ1 receptor-II adenovirus with or without VEGF-C stimulation, since TGF-ββ1 has been shown to have potent antilymphangiogenic effects. Lymphangiogenesis, lymphatic differentiation and cellular proliferation were assessed.Results: Stimulation of ASCs with VEGF-C in vitro significantly increased expression of VEGF-A, VEGF-C and Prox-1. ASCs stimulated with VEGF-C prior to implantation induced a significant (threefold increase) lymphangiogenic response as compared with control groups (unstimulated ASCs or empty Matrigel plugs; p < 0.01). This effect was significantly potentiated when TGF-ββ1 signaling was inhibited using the dominant-negative TGF-ββ1 receptor-II virus (4.5-fold increase; p < 0.01). Stimulation of ASCs with VEGF-C resulted in a marked increase in the number of donor ASCs (twofold; p < 0.01) and increased the number of proliferating cells (sevenfold; p < 0.01) surrounding the Matrigel. ASCs stimulated with VEGF-C expressed podoplanin, a lymphangiogenic cell marker, whereas unstimulated cells did not.Conclusion: Short-term stimulation of ASCs with VEGF-C results in increased expression of VEGF-A, VEGF-C and Prox-1 in vitro and is associated with a marked increase lymphangiogenic response after in vivo implantation. This lymphangiogenic response is significantly potentiated by blocking TGF-ββ1 function. Furthermore, stimulation of ASCs with VEGF-C markedly increases cellular proliferation and cellular survival after in vivo implantation and stimulated cells express podoplanin, a lymphangiogenic cell marker.